Pelatihan Aplikasi Model Pembelajaran Membaca Teks Informasi Untuk Para Guru Bahasa Inggris SMA/SMK/MA Swasta di Kabupaten Lombok Timur - Lalu Thohir; Udin Udin; Mh Isnaini; Lalu Jaswadi Putera (Universitas Mataram, 2022)
In the era of the industrial revolution 4.0 which is characterized by the acceleration of information and technology where information is easily spread throughout the world, teachers have a very important role to prepare students so that they are able to process and understand information well and equipping the students with the skills to read is one of the ways out that teachers need to do. In teaching reading, teachers are required not only to train students' skill to understand texts, but also to train their skill to think actively, creatively and critically and thus, reading learning can provide adequate literacy skills to students. This community service activity aims to socialize the learning model of reading information texts to English teachers from private high schools in East Lombok district as well as train them in applying the model. This activity took place at Al-Badriyah Islamic High School and was attended by 27 teachers. The results of this activity showed that the participants looked enthusiastic and active in participating in the existing series of activities – paying attention and listening to the materials presented by the team, discussions or questions and answers related to presented materials and English learning problems and practicing learning models to read information texts. In addition, the results of the questionnaire for the evaluation of community service activities show that the participants welcomed this activity because they could increase their knowledge and insight, especially those related to teaching reading so that they hoped that there would be similar activities provided in the future.